Opposing effects of SWI/SNF and Mi-2/NuRD chromatin remodeling complexes on epigenetic reprogramming by EBF and Pax5 - Gao, Hua (National Academy of Sciences, 2009)
Transcriptionally silent genes are maintained in inaccessible chromatin. Accessibility of these genes requires their modification by chromatin remodeling complexes (CRCs), which are recruited to promoters by sequence-specific DNA-binding proteins. Early B-cell factor (EBF), which is crucial for B-cell lineage specification, reprograms mb-1 (Ig-α) promoters by increasing chromatin accessibility and initiating the loss of DNA methylation. In turn, this facilitates promoter activation by Pax5. Here, we investigated the roles of ATP-dependent CRCs in these mechanisms. Fusion of EBF and Pax5 with the ligand-binding domain of ERα allowed for 4-hydroxytamoxifen-dependent, synergistic activation of mb-1 transcription in plasmacytoma cells. Knock-down of the SWI/SNF ATPases Brg1 and Brm inhibited transcriptional activation by EBF:ER and Pax5:ER. In contrast, knock-down of the Mi-2/NuRD complex subunit Mi-2β greatly enhanced chromatin accessibility and mb-1 transcription in response to the activators. The reduction of Mi-2β also propagated DNA demethylation in response to EBF:ER and Pax5:ER, resulting in fully unmethylated mb-1 promoters. In EBF- or EBF/Pax5-deficient fetal liver cells, both EBF and Pax5 were required for efficient demethylation of mb-1 promoters. Together, our data suggest that Mi-2/NuRD is important for the maintenance of hypermethylated chromatin in B cells. We conclude that SWI/SNF and Mi-2/NuRD function in opposition to enable or limit the reprogramming of genes by EBF and Pax5 during B-cell development.